Orticochea flap for a massive scalp defect closure in a pediatric patient: literature review and case report - Mendoza Velez, Maria de los Angeles; Macias, Gabriel Sandoval; Cazares, Liliana Aguirre (International Journal of Research in Medical Sciences, 2021)
Scalp defects are still challenging to the surgeon because of the poor elasticity of the soft tissue overlying the calvarium. Defect size, location, and skin characteristics rule the reconstructive options available. Orticochea flap is an excellent option for scalp defects reconstruction. We present a case of a pediatric patient with a massive occipital scalp defect following an animal aggression that was successfully reconstructed with an Orticochea modified flap.